The β-d-Endoglucuronidase Heparanase Is a Danger Molecule That Drives Systemic Inflammation and Correlates with Clinical Course after Open and Endovascular Thoracoabdominal Aortic Aneurysm Repair: Lessons Learnt from Mice and Men - Martin, Lukas; Gombert, Alexander; Chen, Jianmin; Liebens, Julia; Verleger, Julia; Kalder, Johannes; Marx, Gernot; Jacobs, Michael; Thiemermann, Christoph; Schuerholz, Tobias (Frontiers in Immunology, 2017)
Thoracoabdominal aortic aneurysm (TAAA) is a highly lethal disorder requiring open or endovascular TAAA-repair, both of which are rare, but extensive and complex surgical procedures associated with a significant systemic inflammatory response and high post-operative morbidity and mortality. Heparanase is a β-D-endoglucuronidase that remodels the endothelial glycocalyx by degrading heparan sulfate in many diseases/conditions associated with systemic inflammation including sepsis, trauma and major surgery. We hypothesized that a) perioperative serum levels of heparanase and heparan sulfate are associated with the clinical course after open or endovascular TAAA-repair, and b) induce a systemic inflammatory response and renal injury/dysfunction in mice. Using a reverse-translational approach, we assessed a) the serum levels of heparanase, heparan sulfate and the heparan sulfate proteoglycan syndecan-1 preoperatively as well as 6 and 72 hours after intensive care unit (ICU)-admission in patients undergoing open or endovascular TAAA-repair and b) laboratory and clinical parameters and 90-day survival, and c) the systemic inflammatory response and renal injury/dysfunction induced by heparanase and heparan sulfate in mice. When compared to preoperative values, the serum levels of heparanase, heparan sulfate and syndecan-1 significantly transiently increased within 6 hours of ICU-admission and returned to normal within 72 hours after ICU-admission. The kinetics of any observed changes in heparanase, heparan sulfate or syndecan-1 levels, however, did not differ between open and endovascular TAAA–repair. Postoperative heparanase levels positively correlated with noradrenalin dose at 12 hours after ICU-admission and showed a high predictive value of vasopressor requirements within the first 24 hours. Postoperative heparan sulfate showed a strong positive correlation with interleukin-6 levels day 0, 1 and 2 post ICU-admission and a strong negative correlation with lactate clearance during the first 6 hours post ICU-admission. Moreover, systemic administration of heparanase and heparan sulfate induced an inflammatory response and a small degree of renal dysfunction in mice. In conclusion, these results suggest that heparanase and heparan sulfate exhibit a substantial role as clinically relevant danger molecules and may serve as both, promising biomarkers and therapeutic targets in patients undergoing open or endovascular TAAA-repair and, indeed, other conditions associated with significant systemic inflammation.